(untitled) (International Journal of Engineering and Computer Science, 2014)
In Today’s world Data is very important and we are storing our confidential data using the latest technology like –Cloud, Virtualization and BYOD (Bring your own device i.e. Laptop, mobile etc.). We all are storing our confidential data over there .Even there is advancement in the thinking and behaviour of Hackers. Cyber Attack is also a big concern. To overcome all these problems we have ArcSight SIEM (Security Information and Event Management) Technology. Arcsight SIEM will collect, analyse and present information on security products, Operating System, Databases etc. Every data needs to be recorded. So it will monitor all the data coming from different devices and will give you the centralized view of logs